1994
DOI: 10.1017/s0031182000076459
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization ofTheileriaparasites: application to the epidemiology of theileriosis in Zimbabwe

Abstract: Forty Theileria schizont-infected lymphocyte culture isolates from Zimbabwe were characterized using a panel of antischizont monoclonal antibodies (MAbs) and 4 Theileria parva DNA probes containing cloned extrachromosomal element, Tpr repetitive, ribosomal and telomeric sequences. The Theileria isolates were assigned as T. parva or T. taurotragi on the basis of reactivities with MAbs and restriction fragment length polymorphisms (RFLPs) detected using the extra-chromosomal element probe. Cattle-derived T. parv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 30 publications
5
14
0
Order By: Relevance
“…The study by Bishop et al (1994) of field isolates from Zimbabwe showed that cattle-derived parasites were remarkably homogeneous and, in support of this finding, the T. parva Boleni parasite stock, which fits within the general character of these isolates, immunizes very effectively throughout the highveldt where these parasites were isolated. In contrast, buffalo-derived stocks were very heterogeneous (Bishop et al 1994) as had been shown earlier among eastern African buffalo and cattle isolates . A more recent study by Geysen et al (1999) of parasites from the field in the Southern Province of Zambia suggests that one or more parasites with a different genotype from that of local parasites, introduced as part of an immunization campaign in the late 1980s and early 1990s, has become established and is causing disease.…”
Section: Epidemiology Of Diseases Caused By Theileria Parva In Eastersupporting
confidence: 55%
See 1 more Smart Citation
“…The study by Bishop et al (1994) of field isolates from Zimbabwe showed that cattle-derived parasites were remarkably homogeneous and, in support of this finding, the T. parva Boleni parasite stock, which fits within the general character of these isolates, immunizes very effectively throughout the highveldt where these parasites were isolated. In contrast, buffalo-derived stocks were very heterogeneous (Bishop et al 1994) as had been shown earlier among eastern African buffalo and cattle isolates . A more recent study by Geysen et al (1999) of parasites from the field in the Southern Province of Zambia suggests that one or more parasites with a different genotype from that of local parasites, introduced as part of an immunization campaign in the late 1980s and early 1990s, has become established and is causing disease.…”
Section: Epidemiology Of Diseases Caused By Theileria Parva In Eastersupporting
confidence: 55%
“…Also, only one generation of ticks in each year, compared with the three generations in eastern Africa, would have reduced the opportunity for mutation to increase genetic variation (90 generations compared to 270 from 1901). And, from the evidence of heterogeneity in the buffalo isolates (Bishop et al 1994), there must have been very limited or no migration of buffalo genotypes to the highveldt cattle environment. Thus the case for conditions leading to homogeneity in cattle-derived T. parva genotypes in the highveldt environment seems sound, but why is there such diversity in the buffalo genotypes that started from the same sample of parasites?…”
Section: Epidemiology Of Diseases Caused By Theileria Parva In Eastermentioning
confidence: 99%
“…This would, in turn, be expected to promote co-infection with a comparatively higher number of parasite genotypes in buffalo. A high level of genetic diversity has previously been observed in buffalo samples (Bishop et al, , 1994Collins and Allsopp, 1999) and this has lead to speculation that the buffalo-associated T. parva population may represent a more diverse gene pool (Collins and Allsopp, 1999). Thus, a high background level of diversity in the buffaloassociated population may make it easier to discriminate between multiple co-infecting genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Cattle-tick-cattle transmission is thought to be limited as erythrocytic piroplasms are either absent or at an insufficient level to infect new ticks. The use of molecular characterisation tools has revealed a high level of diversity among buffalo-derived T. parva stocks compared to cattle-derived T. parva stocks (Bishop et al, 1994;Collins and Allsopp, 1999;Geysen et al, 2004;Oura et al, 2004a). Thus, there is growing evidence that only a limited subset of the total T. parva gene pool present within buffalo has become established in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unknown whether the T. parva parasite is genetically 'transformed' as it adapts to the bovine host or whether there is selection of an individual strain that causes ECF-like clinical signs from a mixed population of genotypes in the buffalo. The use of molecular characterisation tools has revealed a high level of diversity among buffalo-derived T. parva stocks compared to cattle-derived T. parva stocks (Bishop et al 1994;Collins and Allsopp 1999;Geysen et al 2004;Oura et al 2004a). Thus, there is a growing body of evidence that only a limited subset of the total T. parva gene pool present within buffalo has become established in cattle.…”
Section: Introductionmentioning
confidence: 99%